IMPORTANCE OF INDEPENDENT ASSIGNMENTS IN EDUCATIONAL ACTIVITIES - Ishpulatova Dinora; Yarmanova Yulduz Burievna (American Journals, 2025)
This article discusses the educational and educational significance of independent work in activating students' cognitive activity. It also discusses the educational and educational significance of independent work and the types of independent work.
Keywords: Teacher, student, content, goal, cognitive activity, independent work, attitude, result, elementary school students, activation.